Current Status: Mexican Medicinal Plants with Insecticidal Potential - Guzmán-Pantoja, Ludmila Elisa; Lina-García, Laura P.; Bustos-Zagal, Graciela; Hernández-Velázquez, Víctor M. (IntechOpen, 2012)
None